2020
DOI: 10.4317/jced.57091
|View full text |Cite|
|
Sign up to set email alerts
|

Oral leukoplakia, a clinical-histopathological study in 412 patients

Abstract: Background A retrospective clinical-histopathological study was made of the evolution of oral leukoplakia over time, staging the disease according to the classification of van der Waal. Material and Methods A study was made of 412 patients with oral leukoplakia, analyzing the corresponding clinical factors and histopathological findings; assessing associations between the different clinical presentations and epithelial dysplasia; and evaluating the factors influencing m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

12
17
4

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(33 citation statements)
references
References 29 publications
12
17
4
Order By: Relevance
“…It has been reported in the literature that, clinically, leukoplakia usually presents as a homogeneous lesion. Scheifele et al observed homogeneous leukoplakia to clearly predominate (86.8%) as compared to non-homogenous type, 8 similarly, Rubert et al, found in their study that 81.6% of the patients were having homogeneous type of oral leukoplakia, in accordance to this, most of the cases in our study were found to be of homogenous leukoplakia [9] . In our study, majority of the cases which were diagnosed clinically diagnosed as leukoplakia presented a histological diagnosis of hyperkeratosis (45%) mild epithelial dysplasia (33.33%), which suggests a less aggressive nature.…”
Section: Discussionsupporting
confidence: 87%
“…It has been reported in the literature that, clinically, leukoplakia usually presents as a homogeneous lesion. Scheifele et al observed homogeneous leukoplakia to clearly predominate (86.8%) as compared to non-homogenous type, 8 similarly, Rubert et al, found in their study that 81.6% of the patients were having homogeneous type of oral leukoplakia, in accordance to this, most of the cases in our study were found to be of homogenous leukoplakia [9] . In our study, majority of the cases which were diagnosed clinically diagnosed as leukoplakia presented a histological diagnosis of hyperkeratosis (45%) mild epithelial dysplasia (33.33%), which suggests a less aggressive nature.…”
Section: Discussionsupporting
confidence: 87%
“…It is well established that the risk of malignant transformation is significantly associated to the localization of OLP. Thus, OLP, which developed on the tongue or at the floor of mouth progress more often into malignancy as OLP at other sides of the oral cavity [ 53 ]. Additionally, positive PD-L1 staining was significantly more likely in tongue squamous cell carcinomas [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…In this study the age of patients also did not influence the risk of malignant transformation [ 28 ]. On the other hand, in retrospective research conducted by Rubert et al, in a group of 412 patients diagnosed with oral leukoplakia, females (281) predominated over males (131) [ 29 ]. In that research most patients (53.2%) were also non-smokers and did not consume alcohol (85%).…”
Section: Discussionmentioning
confidence: 99%
“…In the study, 57.1% of cases were diagnosed among female patients and 42.9% among male patients, which may lead to a conclusion that female patients might be more prone to malignant transformation of oral leukoplakia [ 29 ], which is the opposite result of the research conducted by Jayasooriya et al [ 28 ], Wang et al [ 27 ], and meta-analysis prepared by Matulić et al, which also revealed that there were no statistically significant differences in malignant transformation of oral leukoplakia between male and female patients [ 30 ]. Nevertheless, returning to the statement that the age of patients may influence the clinical symptoms of leukoplakia, the study by Rupert et al also seems to confirm this [ 29 ]. In their research, patients with clinically non-homogeneous lesions were older and lesions of non-homogeneous leukoplakia were larger than clinically homogenous to a statistically significant degree.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation